Hallmarks of primary headache: part 1 – migraine - Raggi, Alberto; Leonardi, Matilde; Arruda, Marco; Caponnetto, Valeria; Castaldo, Matteo; Coppola, Gianluca; Della Pietra, Adriana; Fan, Xiangning; Garcia-Azorin, David; Gazerani, Parisa; Grangeon, Lou; Grazzi, Licia; et al. (Journal of headache and pain, 2024)
Background and aim Migraine is a common disabling conditions which, globally, affects 15.2% of the population. It is the second cause of health loss in terms of years lived with disability, the first among women. Despite being so common, it is poorly recognised and too often undertreated. Specialty centres and neurologists with specific expertise on headache disorders have the knowledge to provide specific care: however, those who do not regularly treat patients with migraine will benefit from a synopsis on the most relevant and updated information about this condition. This paper presents a comprehensive view on the hallmarks of migraine, from genetics and diagnostic markers, up to treatments and societal impact, and reports the elements that identify migraine specific features. Main results The most relevant hallmark of migraine is that it has common and individual features together. Besides the known clinical manifestations, migraine presentation is heterogeneous with regard to frequency of attacks, presence of aura, response to therapy, associated comorbidities or other symptoms, which likely reflect migraine heterogeneous genetic and molecular basis. The amount of therapies for acute and for prophylactic treatment is really wide, and one of the difficulties is with finding the best treatment for the single patient. In addition to this, patients carry out different daily life activities, and might show lifestyle habits which are not entirely adequate to manage migraine day by day. Education will be more and more important as a strategy of brain health promotion, because this will enable reducing the amount of subjects needing specialty care, thus leaving it to those who require it in reason of refractory condition or presence of comorbidities. Conclusions Recognizing the hallmarks of migraine and the features of single patients enables prescribing specific pharmacological and non-pharmacological treatments. Medical research on headaches today particularly suffers from the syndrome of single-disease approach, but it is important to have a cross-sectional and joint vision with other close specialties, in order to treat our patients with a comprehensive approach that a heterogeneous condition like migraine requires.